Genome-wide identification of growth-regulating factors in moso bamboo (Phyllostachys edulis): in silico and experimental analyses - Shi,Yanan; Liu,Huanlong; Gao,Yameng; Wang,Yujiao; Wu,Min; Xiang,Yan (PeerJ, 2019)
Growth-regulating factor (GRF), a small plant-specific transcription factor (TF) family, is extensively involved in the regulation of growth and developmental processes. However, the GRF family has not been comprehensively studied in moso bamboo (Phyllostachys edulis), a typical non-timber forest member. Here, 18 GRF genes were identified and characterized from the moso bamboo genome, and they clustered into three subfamilies (A, B and C). PeGRF genes were analyzed to determine their gene structures, conserved motifs and promoter. The non-synonymous/synonymous substitution ratios of paralogous and orthologous were less than 1, indicating that the GRF family mainly experienced purifying selection during evolution. According to the analysis of tissue-specific expression patterns, the participation of moso bamboo GRFs might be required during the formation and development of these five tissues. Moreover, PeGRF proteins might be involved in the regulation of plant development in biological processes. The qRT-PCR analysis demonstrated that PeGRF genes played essential roles in combating hormonal stresses and they might be involved in hormone regulation. PeGRF11, a nuclear localized protein as assessed by a subcellular localization assay, could interact with PeGIF3 in yeast and in planta according to yeast two-hybridization and bimolecular fluorescence complementation assays (BiFC) assays. But PeGRF11, as a TF, had no transcriptional activity in yeast. These results provide useful information for future functional research on the GRF genes in moso bamboo.
Keywords: Moso bamboo; GRFs; Transcription activity; Yeast two-hybridization assay; BiFC